The Effect of Industrial Existence on the Environment and Socio-Economy - Amin Pujiati; Mohamad Imron (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
The purpose of this study is to analyze the influence of industry on the water quality index, air quality index, land cover quality index, population health complaints, and gross domestic product. This study uses quantitative methods with panel data, which is a combination of cross section data from 30 provinces in Indonesia and time series for the period 2013-2017. The analytical method used is structural equation model-partial least squares. The results showed that the industry had a significant negative effect on the water quality index, air quality index, and land cover quality index. While the industry has a significant positive effect on population health complaints and gross domestic product. The conclusion from this study is that the industry is more likely to have a negative impact on the environment and social, while the positive impact is more likely to affect the economy. Advice for the government is the need for industrial development efforts accompanied by improvements in environmental quality to maintain system balance.